A Comparative Descriptive Analysis of Routine Hematological Profiles in First-Trimester Incomplete Abortion and Anembryonic Pregnancy - Indira Putri Fiana Dewi; Adang Muhammad Gugun (International Medical Journal Corp. Ltd, 2025)
Introduction: Early pregnancy loss presents in diverse forms, yet a direct comparison of routine hematological profiles between incomplete abortion and anembryonic pregnancy is not well-documented. This study aimed to provide a descriptive comparison of these profiles to highlight potential differences linked to their distinct pathophysiology. Methods: A retrospective, descriptive study was conducted on 60 first-trimester patients: 30 with incomplete abortion and 30 with anembryonic pregnancy. The analysis focused on leukocyte count, platelet count, bleeding time (BT), and clotting time (CT), using descriptive statistics to compare the two cohorts. Results: The incomplete abortion group showed a higher mean leukocyte count (10,883 /µL) and a wider range (6,400–20,100 /µL) compared to the anembryonic pregnancy group (10,110 /µL; range 4,800–17,900 /µL). Mean platelet counts were also slightly higher in the incomplete abortion group. BT and CT were normal and nearly identical between groups. Discussion: The pronounced leukocytosis in the incomplete abortion group is consistent with the greater inflammatory and hemorrhagic nature of this condition. In contrast, the more quiescent hematological profile of anembryonic pregnancy reflects its state as a silent, or